The Effective Use of Portland Cement in Reactive Powder Hybrid Asphalt Concrete - (:unkn) unknown (My University, 2019)
Today, building a durable and cost-efficient infrastructure while minimizing future repair needs is a challenging task, and innovative technological breakthroughs are needed. Limited research has been conducted to investigate the use of portland cement (PC) to improve the performance of asphalt pavements. Portland cement in bitumen materials is attractive as it can improve the performance and reduce costs. Warm Mix Asphalt (WMA) is also an attractive alternative to Hot Mix Asphalt (HMA) as this material produces tremendous energy savings by lowering the production temperatures and enhances certain performance characteristics. It can be envisioned that the use of portland cement incorporated into an asphalt matrix can result in a hybrid product with enhanced long-term performance (especially in wet environments) characterized by better salt-scaling, freeze-thaw resistance, and self-healing properties (thermally-induced and moisture-induced). This study explores the interactions and compatibility of different types of portland cements with bitumen binders and identifies the potential improvement of performance in WMA portland cement hybrid systems. The objectives of this research were to identify and characterize 5 portland cements used as reactive powders compounds: Lafarge Type I (LF), St. Mary Type I (SM), Buzzi Unicem CSA (CSA), Lafarge Oil Well (OW), and Kerneos High Alumina (HA), 1 Weston spray dryer absorber (SDA), and 1 Payne & Dolan control limestone filler (LS) and determine how these materials were compatible with asphalt binders. The effect of the chemical properties, physical properties, and mineralogical composition of all powders performance of mastics based on different asphalt binders is discussed. The powders were mixed with asphalt binders (PG58-28 and PG52-34) at 0, 5, 15, 25% concentration by volume with a variable blade speed mixer and these mixtures were modified with a Warm Mix Asphalt (WMA) additive (Evotherm by Ingevity®). Rheological properties were investigated using a Dynamic Shear Rheometer (DSR). Complex Shear Modulus (G*) and Phase Angle () parameters were obtained for the mastics (binders with fillers). It was demonstrated that the addition of powders at 15% and higher dosages significantly affected the stiffness. Performance related indicators were determined for viscosity using the Brookfield Rotational Viscometer and rutting (G*/sin(δ)), Multiple Stress Creep and Recovery (Jnr and % Recovery), fatigue (G*sin(δ)), and aging resistance (aging index) using the DSR. Thermal cracking (S(t) and m-value) was evaluated at low temperatures with the Bending Beam Rheometer. All reactive powder (cement based) and SDA mastics were compared to control limestone mastics. LF mastics were comparable to the control for rutting resistance but enhanced the low-temperature performance. SM mastics were also comparable for rutting resistance and comparable for low-temperature evaluations. CSA mastics enhanced the rutting resistance, aging resistance, and low-temperature thermal cracking resistance and at the same time did not hinder the fatigue resistance. OW mastics resembled similarities for workability, rutting resistance, and low-temperature testing. HA mastics demonstrated improvements for rutting resistance and did not hinder thermal cracking resistance. SDA mastics improved the rutting resistance and demonstrated comparable results for fatigue resistance, aging resistance, and thermal cracking resistance. A subset of 2 reactive powders (LF and CSA) were used at an optimized dosage of 25% concentration by volume binder replacement with WMA PG58-28 and WMA PG52-34 binders to evaluate and analyze the effect on typical Superpave® mixture testing such as mixture workability (%Gmm) and aging resistance (aging index) using a Superpave® Gyratory Compactor, moisture damage resistance (IDT) using an Indirect Tensile Machine, and fatigue (E*) and thermal cracking (S(t)) using a MTS environmental chamber. Durability testing was performed to evaluate freeze-thaw (mass change) and salt-scaling (mass loss). The results demonstrated that CSA mixtures enhanced the freeze-thaw performance, however, the results from the salt-scaling testing were inconclusive. Overall, the results of the mixture performance testing overwhelmingly supported the observations from the mastic stage testing. Statistical analysis was evaluated to correlate the physical and chemical properties with rheological performance. It was observed that Rigden voids, specific gravity, Na2O, and P2O5 had the best correlation to rheology, viscosity, and rutting resistance. As Rigden voids, Na2O, and P2O5 increased in concentration the stiffness of the mastics increased, and as specific gravity increased in concentration the stiffness of the mastic decreased. The results of this research puts significant confidence in utilization of portland cement reactive powders in asphaltic pavements. The next steps are crucial to build on these finding and encourage the paving industry to adopt portland cement powders. The mechanism of the physio-chemical interaction between the reactive powders and the asphalt binder must be evaluated using further testing to quantify the effects of portland cement and promote it as a binder enhancer for commercial use.
Keywords: asphalt; portland cement; reactive powder; self healing; spray dryer absorber; warm mix asphalt